Pavlovian Olfactory Fear Conditioning: Its Neural Circuity and Importance for Understanding Clinical Fear-Based Disorders - Hakim, Marziah; Battle, Andrew R.; Belmer, Arnauld; Bartlett, Selena E.; Johnson, Luke R.; Chehrehasa, Fatemeh (Frontiers in Molecular Neuroscience, 2019)
Odors have proven to be the most resilient trigger for memories of high emotional saliency. Fear associated olfactory memories pose a detrimental threat of potentially transforming into severe mental illness such as fear and anxiety related disorders. Many studies have deliberated on auditory, visual and general contextual fear memory processes; however, fewer studies have investigated mechanisms of olfactory fear memory. Evidence strongly suggests that the neuroanatomical representation of olfactory fear memory differs from that of auditory and visual fear memory. The aim of this review is to revisit the literature regarding the understanding of the neurobiological process of fear conditioning and to illustrate the circuitry of olfactory fear memory.